Integrating audio technology and FFT analysis to explore microtonality and the "missing fundamental" in kacapi siter - Hafizhah Insani Midyanti; Yudi Sukmayadi; Munir; Julia; Fensy Sella; Abizar Algifari Saiful; Dwi Marisa Midyanti (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2025)
The Sundanese Kacapi Siter exhibits distinctive microtonal characteristics and acoustic phenomena requiring objective documentation. This study integrates high-fidelity audio recording with Fast Fourier Transform (FFT) analysis to examine the microtonal properties of the Pelog Sunda tuning system and the missing fundamental phenomenon in this traditional instrument. Using Practice-Led Research methodology, we recorded 20 single-note samples with a Neumann TLM 103 condenser microphone in natural reflective classroom conditions, analyzing them through SPAN FFT spectral analysis and cent deviation calculations against 12-TET standards. Results demonstrate systematic microtonality with deviations ranging from -15 to +28 cents, with note "Ti" consistently sharp (+17 to +28 cents) and note "Na" consistently flat (-5 to -13 cents) across octaves (p<0.001, effect size d=2.4). Spectral analysis reveals a missing fundamental phenomenon in low-register notes (La 4: 58.2 Hz, Ti 4: 66.5 Hz), where harmonics dominate perceived pitch despite weak fundamental-frequency energy (-14.3 to -8.9 dBFS fundamental vs. -6.2 to -4.1 dBFS second harmonic). These findings provide quantitative evidence that Sundanese tuning represents a structured non-Western pitch system with intentional microtonal design, advancing computational ethnomusicology through objective acoustic documentation methods that enable preservation, comparative analysis, and technological applications in digital instrument development.